KONSEP KETENTRAMAN HIDUP PERSPEKTIF BUYA HAMKA DALAM TAFSIR AL-AZHAR - Muhammad Giffary Salman Maulidan (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2026)
Peace is a condition in the heart that feels so very calm, which is caused by a relationship between the creature and the kholik. A relationship that is carried out between the creature and the kholik through the way of dhikr, in the tafsir of al-azhar, buya hamka explains about QS. Ar-Ra'd Verse 28 when a person has faith in him, then he will always remember himself to the kholik in any condition, whether in a happy or difficult situation. By always dhikr to Allah, a person's heart will feel calmer, there is no anxiety, fear, anxiety, doubt, etc. and when we always remember ourselves to Allah by doing dhikr, Allah will give peace in our lives according to His words in QS. Ar-Ra'd: 28